PEMANFAATAN HORMON TUMBUH ORGANIK UNTUK MENINGKATKAN PRDUKTIVITAS SINGKONG HASIL EKSPLORASI SELEKSI BIBIT UNGGUL - Tri Waluyo (Universitas Nasional, 2020)
Cassava is a superior commodity that is feasible to be developed in Indonesia, because it has the potential as a raw material for various processed products. In addition, the availability of extensive land, climate and land is suitable for developing cassava commodities. Moreover, this plant can grow well in the high and lowlands and knows no season. Therefore, Indonesia has a huge potential to develop cassava based products. The development of processed cassava products will support food sovereignty and improve community welfare. This study aims to find several types of cassava with high productivity that are resistant to drought and pest attacks, produce the right combination of fertilization and growth hormones to increase cassava production by more than 40 tons per hectare, find superior cassava varieties with productivity of more than 40 tons per hectare and analyze the financial feasibility of cassava farming. This research was conducted by surveying the types of cassava, cassava productivity, cropping patterns, land area, and prices at the farmer and trader level in West Java Province. The questionnaire was submitted to farmers to obtain information on genotype / clone identities, local names, where to obtain seedlings, and reasons for choosing them as well as cultivation technique data (cultivation methods, plant maintenance, and harvesting). Selection of superior seeds for types of cassava with productivity more than 40 tonnes / ha. The survey results will obtain four types of cassava with high productivity and adaptive. The four types of cassava will be tested with four semi-organic fertilization treatments and growth hormone (Bio-Extreme Granule, Organox, Hormax, Bomax and milk powder). There are 4 levels of fertilization treatment, namely chicken manure 10 tonnes / ha, chicken manure 10 tonnes / ha using granule and organox bio-extremes, chicken manure 15 tonnes / ha and fertilization with granule bio-extremes 2 tonnes / ha and organox. The cultivation of elephant and manggu cassava, the results of which were planted using manure and organic hormones, turned out to increase the average production for manggu varieties by 26.50 tons / ha, while for Jurnal Ilmu dan Budaya, Edisi Khusus Berlian RI 75 Tahun 8208 | JURNAL ILMU DAN BUDAYA elephant varieties there was an increase in the average production of 40.50 tons / ha. The cultivation of elephant and manggu cassava with manure and organic hormone fertilization is feasible with R / C ratio values of 2.94 and 3.72.